2014
DOI: 10.1364/josab.31.0000a6
|View full text |Cite
|
Sign up to set email alerts
|

Interference theory of multiple optical vortex states in spiral phase plate etalon: thick-plate and thin-plate approximation

Abstract: The spiral phase plate etalon transmission function is calculated from the low-reflectivity to high-reflectivity regime. Two approximations are considered: thick-plate approximation and thin-plate approximation. The thick-plate approximation explicitly takes into account the angle between the azimuthally increasing surface and the flat surface, while the thin-plate approximation does not. The two results are in agreement in the low-reflectivity regime, but not in the high-reflectivity regime. The thick-plate a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 48 publications
1
9
0
Order By: Relevance
“…10(c)] reproduces the simulated intensity distribution. Even if an antireflection coating was not present on the surface of the analyzed SPPs, the far-field intensity pattern appears not to be affected by an azimuthal modulation due to multiple internal reflections, as predicted and described in recent literature [31][32][33][34]. On the other hand, this effect could have been hidden by the noise due to signal fluctuation and further analyses could be required in order to unveil this phenomenon [33].…”
Section: Resultssupporting
confidence: 60%
“…10(c)] reproduces the simulated intensity distribution. Even if an antireflection coating was not present on the surface of the analyzed SPPs, the far-field intensity pattern appears not to be affected by an azimuthal modulation due to multiple internal reflections, as predicted and described in recent literature [31][32][33][34]. On the other hand, this effect could have been hidden by the noise due to signal fluctuation and further analyses could be required in order to unveil this phenomenon [33].…”
Section: Resultssupporting
confidence: 60%
“…67 The thin-plate approximation does not explicitly take into account the angle between the flat surface and azimuthally increasing step height, while the thick-plate approximation explicitly takes this angle into consideration. 67 The thin-plate approximation does not explicitly take into account the angle between the flat surface and azimuthally increasing step height, while the thick-plate approximation explicitly takes this angle into consideration.…”
Section: Thick-plate and Thin-plate Approximationsmentioning
confidence: 99%
“…As the output intensity of an SPP etalon in the thick-plate approximation and thin-plate approximation has been previously calculated, 67 this section provides a summary of the main results. It has been shown that in the low finesse regime (i.e., low surface reflectivity regime) of an SPP etalon, the output intensity in the thin-plate approximation and thickplate approximation provides consistent results.…”
Section: Thick-plate and Thin-plate Approximationsmentioning
confidence: 99%
See 2 more Smart Citations